Design strategy of electrode patterns based on finite element analysis in microfluidic device for Trans‐Epithelial Electrical Resistance (TEER) measurement. Issue 2 (25th November 2020) - Miyazaki, Takashi; Hirai, Yoshikazu; Kamei, Ken‐ichiro; Tsuchiya, Toshiyuki; Tabata, Osamu
Abstract: Trans‐epithelial electrical resistance (TEER) is a widely used non‐invasive and label‐free measurement to evaluate the barrier function of mono‐layered cells in real‐time. However, TEER values depend on distribution of electric current densities generated by a combination of shapes and arrangements of plane electrodes for performing TEER, but until now, there is no systematical analysis of their effects on TEER values, causing less reproducibility. Here, we report a new strategy to design the shapes and arrangements of electrodes to perform TEER in a microfluidic device. To investigate the effects of the electrodes design on TEER values, we analyze the distribution of electric current densities using finite element method and evaluate their uniformity of sensitivity. Our strategy allowed designing several electrode patterns of electrodes combinations, capable of simultaneous cell observation with a microscope and TEER measurements.